2019
DOI: 10.3390/rs11131514
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vegetation Thresholds for Assessing Land Use and Land Use Changes in Cambodia using the Google Earth Engine Cloud-Computing Platform

Abstract: As more data and technologies become available, it is important that a simple method is developed for the assessment of land use changes because of the global need to understand the potential climate mitigation that could result from a reduction in deforestation and forest degradation in the tropics. Here, we determined the threshold values of vegetation types to classify land use categories in Cambodia through the analysis of phenological behaviors and the development of a robust phenology-based threshold cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 95 publications
0
68
0
Order By: Relevance
“…This fact can also be deduced from Table 1. CC can be recorded with many different methods: by synoptic naked-eye observations (Lau & Crane 1997;Bréon & Colzy 1999;Norris 1999), by using lidar and radar methods (Intrieri et al 2002), by using an "All Sky Camera" (Ackerman & Cox 1981;Pfister et al 2003;Long et al 2006) or using satellite monitoring (Venkatappa et al 2019).…”
Section: Cloud Coverage -Ccmentioning
confidence: 99%
“…This fact can also be deduced from Table 1. CC can be recorded with many different methods: by synoptic naked-eye observations (Lau & Crane 1997;Bréon & Colzy 1999;Norris 1999), by using lidar and radar methods (Intrieri et al 2002), by using an "All Sky Camera" (Ackerman & Cox 1981;Pfister et al 2003;Long et al 2006) or using satellite monitoring (Venkatappa et al 2019).…”
Section: Cloud Coverage -Ccmentioning
confidence: 99%
“…Hence, sub-pixel analysis may be useful to overcome these mixed pixel problems in future studies. In addition, compared to LULC mapping, using a Google Earth Engine-like platform [56,57], the proposed method is still a time-consuming and laborious work.…”
Section: Advantages and Disadvantages Of The Proposed Frameworkmentioning
confidence: 99%
“…Satellite remote sensing technologies provide an alternative approach to MRV tasks required for the REDD+ scheme in developing countries in the tropics, where the availability of field measurements is sparse [19]. In recent years, phenology-based classification methods using spectral remote sensing data and the enhanced vegetation index (EVI) have shown satisfactory accuracy [20][21][22][23][24]. Previous research [24,25] has shown promising results with high reliability and accuracy for vegetation [26], cropland [27] and land cover mapping [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, phenology-based classification methods using spectral remote sensing data and the enhanced vegetation index (EVI) have shown satisfactory accuracy [20][21][22][23][24]. Previous research [24,25] has shown promising results with high reliability and accuracy for vegetation [26], cropland [27] and land cover mapping [24,28]. The most recent studies classified land cover categories and changes using the moderate to high spatial resolution of the Landsat remote sensing data [24,29,30].…”
Section: Introductionmentioning
confidence: 99%